Sidescan sonar survey (300 kHz) during R/V Heincke cruise HE474 in the German Bight with link to raw data files - Hass, H Christian; Papenmeier, Svenja (Alfred Wegener Institute - Wadden Sea Station Sylt, 2019)
Sidescan sonar data were collected during R/V Heincke cruise HE474 with a towed multi pulse Edgetech 4200-MP. Data recording was executed along 50 parallel profiles in North Sea within German EEZ. The survey speed was 4-5 knots and the swath set to 150 / 460 m to obtain a resolution of 25 cm / ~1 m along track. In total 355 km² were area-wide mapped. The interpreted sediment distribution map of this data area published in the GeoSeaPortal of the Federal Maritime and Hydrographic Agency (Papenmeier, S., Hass, H.C., Propp, C., Thiesen, M., Zeiler, M.: Verteilung der Sedimenttypen auf dem Meeresboden in der deutschen AWZ (1:10.000). www.geoseaportal.de, 2018).